The Effect of Water Corrosion and Shot Peening on Fatigue Strength of Mining Drill Rods - T. W. Wlodek (Canadian Institute of Mining, Metallurgy and Petroleum, 1952)
"AbstractThe results of research into the fatigue properties of SAE 1080 carbon steel and nickel-chromium-molylbdenum steel for mining drill rods are analysed and described in detail.The effect of water corrosion on the fatigue strength of drill rods of these two steels in the as-rolled condition has ,been investigated and the beneficial influence of shot-peening on their dry and water-corrosion fatigue strengths determined by employing the method developed previously (1).Eight S-N curves for as-rolled and shot-peened mining drill rods under both dry and water corrosion conditions have been derived and their shape and relative position are discussed. The main features relating to field performance of the drill rods are analysed.Purpose of Research and Outline of ProgrammeDRILLING holes in rock and ore by means of drill rods attached to a pneumatic drill is a basic procedure required in mining operations. Detonation of explosives placed in these holes is at present the only practical method of breaking down the rock and ore.A drilling rod is supported by its bit end in the drilled rock. Its shank end, fixed in the drilling machine, transmits impact energy to the cutting edges of the bit. On the field performance of the drill rod depend a number of basic mining operations such as sinking, drifting, and stoping. The drill rod is there-fore regarded as one of the most important tools used in the mining industry."